Geomechanical properties evaluation of Mauddud formation based on experimental measurements and well log data - Al-jumaili, Mohammed Almojahed F.; Al-Ameri, Nagham J. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Mauddud formation is one of the most prominent formations in Northeastern Iraq due to its significant hydrocarbon reserves, making accurate geomechanical characterization essential for safe drilling operations and informed development planning. This study constructs a calibrated post-drill one dimensional mechanical earth model (1D-MEM) for selected wells, levering Techlog software to integrate rock mechanical data, image logs, multi-arm caliper measurements, conventional well logs, drilling reports, and core analyses. The methodology provides a detailed workflow for estimating geomechanical properties from log and image analysis to model calibration. Validation of the 1-D MEM performed through cross-comparison with direct measurements, ensuring the reliability of the predicted stress and strength profile. Laboratory and field data including pore pressure measurements using DST method, destructive and non-destructive mechanical tests, scanning electron microscopy (SEM), thin section test (TS), X-ray diffraction test (XRD), and energy-dispersive X-ray spectroscopy (EDS) have all been used for analyzation and calibration process. These datasets enhance the MEM parameters and support the derivation of empirical correlation specific to the Mauddud Formation. Derived correlations include compressional-shear slowness velocity, slowness velocity- bulk density, compression slowness-unconfined compressive strength (UCS), and the Young’s modulus to UCS correlation. Results show that mineralogical composition particularly porosity and calcite content have a dominant influence on formation strength with high porosity, low calcite intervals resulting in the lowest UCS values.